الإثبات في عقود التجارة الإلكترونية: دراسة مقارنة القضاء الليبي نموذجا - Othman Abdusalam Begdadi
The fast paced spread of using new communication media as a way of making deals or transaction has brought what is known as E-electronic contracts. The emergence of of this trends has called for legal inquires especially in the area of documentation or proof since complexity of relationship is high in this kind of contracts. The difference of physical environment in which these contracts are held and issues also called for determination. Depending on what is written and issued on these electronic documents the question still is about the reliability of this document. The situation becomes even worse if one of the contractual parties used this E-document as a full proof of contract. Moreover electronic signature is also part of this controversy which also presents a lot of inquires. Because there is no any legislation which organizes this kind of transactions and the lack of evidence to approve it in the Libyan law. The researcher must refer to the general rules in order to e able to answer thee inquires and will also work through this topic to answer all these kinds of inquires about E-electronic transactions. These inquires are better answered through comparing and contrasting between the basis and rules that has a connection with this issue in the proof of law in civil and commercial transaction to ensure the degree of interference and cohesion of the kinds of electronic transaction with daily life, developments and technology developments. The issue of electronic contract has flowed to the surface so there must be a deep legal investigation to conduct these contracts through new communication media. Based on the mentioned above, the researcher has decided to choose “The proof in electronic commerce contracts” comparative study taking Libyan judicial system as a model.